Protocol of sterile personal protective equipment for surgical personnel against SARS-CoV-2 during the COVID-19 pandemic - Guevara Valmana, Osvaldo I.; Quero, Maria M. Cavazos; Loaeza, Elias Gil; Sandoval, Jesus C. Lopez; Molina, Jose A. Pereyra; Ceballos, Mario A. Rebolledo; Chavez, Chantal Gonzalez; Gachuz, Omar D. Gonzalez (International Journal of Research in Medical Sciences, 2020)
Background: COVID-19 represents the major pandemic seen the last years generating morbidity and mortality around the world. It is well known the propagation of the virus occurs by air mostly, so it is needed a barrier when the medic personal is treating suspect or confirm patients. Personal protective equipment represents a barrier between the health personnel and the patient during the COVID-19 pandemic. The surgical team during a COVID-19 confirmed o suspicious case procedure requires using PPE to be protected and keep the sterility for the patient safety. Methods: A team of surgeons from a 100% COVID-19 hospital of the Mexican institute of social security developed an inner protocol of safe use PPE maintaining sterility for the surgery. Conclusions: The protocol described provides safety to surgical team and the patient minimizing risk of surgical infections.